Does parental divorce moderate the heritability of body dissatisfaction? An extension of previous gene–environment interaction effects. Issue 2 (28th August 2015) - O'Connor, Shannon M.; Klump, Kelly L.; VanHuysse, Jessica L.; McGue, Matt; Iacono, William
ABSTRACT: Objective: Previous research suggests that parental divorce moderates genetic influences on body dissatisfaction. Specifically, the heritability of body dissatisfaction is higher in children of divorced versus intact families, suggesting possible gene–environment interaction effects. However, prior research is limited to a single, self‐reported measure of body dissatisfaction. The primary aim of this study was to examine whether these findings extend to a different dimension of body dissatisfaction: body image perceptions. Method: Participants were 1, 534 female twins from the Minnesota Twin Family Study, aged 16–20 years. The Body Rating Scale (BRS) was used to assess body image perceptions. Results: Although BRS scores were heritable in twins from divorced and intact families, the heritability estimates in the divorced group were not significantly greater than estimates in the intact group. However, there were differences in nonshared environmental effects, where the magnitude of these environmental influences was larger in the divorced as compared with the intact families. Discussion: Different dimensions of body dissatisfaction (i.e., negative self‐evaluation versus body image perceptions) may interact with environmental risk, such as parental divorce, in discrete ways. Future research should examine this possibility and explore differential gene–environment interactions using diverse measures. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:188–192).